1989
DOI: 10.1111/j.1476-5381.1989.tb16874.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular platelet‐activating factor regulates eicosanoid generation in guinea‐pig resident peritoneal macrophages

Abstract: 1 The role of intracellular platelet-activating factor (Pat) in arachidonic -acid (AA) mobilization from guinea-pig peritoneal macrophages has been investigated by use of the potent and selective Paf receptor antagonists, WEB 2086 and CV 6209. 2 Adherent macrophages contained cell-associated Paf which was increased by exposure to formyl-methionyl-leucyl-phenylalanine (fMLP), endotoxin and the ionophore, A23187. However, only endotoxin and A23187 caused release of detectable amounts of Paf into the extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…We have previously found that this extraction gives a recovery of 94% from Tyrode's buffer [28], The extracts were subjected to centrifugation (5 min, 1,000 g) to remove the precipitate, and the supernatants were evaporated to dry ness under reduced pressure. The dried extracts were reconstituted in 200 pi of Tyrode's buffer (pH 7.4) containing 0.25% w/v BSA before PAF assay.…”
Section: Bioassay Ofpafmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found that this extraction gives a recovery of 94% from Tyrode's buffer [28], The extracts were subjected to centrifugation (5 min, 1,000 g) to remove the precipitate, and the supernatants were evaporated to dry ness under reduced pressure. The dried extracts were reconstituted in 200 pi of Tyrode's buffer (pH 7.4) containing 0.25% w/v BSA before PAF assay.…”
Section: Bioassay Ofpafmentioning
confidence: 99%
“…The dried extracts were reconstituted in 200 pi of Tyrode's buffer (pH 7.4) containing 0.25% w/v BSA before PAF assay. The amount of PAF was assayed by platelet aggregation at 37°C using a 540 ChronoLog aggregometer (Chrono-Log, USA) as described by Stewart and Phillips [28]. The reference cells contained a 1 in 10 dilution of platelets in Tyrodc's buffer (pH 7.4) containing 0.25% w/v BSA.…”
Section: Bioassay Ofpafmentioning
confidence: 99%
“…However, unlike other lipid mediators (e.g., prostaglandins and lipoxygenase products), once formed, PAF is often retained in cells (4)(5)(6). This cellular retention is a prominent feature of stimulus-evoked PAF and may underlie intracellular functions (4,7,8). When PAF is added to cells (e.g., washed rabbit platelets), it is rapidly internalized (9).…”
mentioning
confidence: 99%
“…Nevertheless, the se lective, potent and structurally distinct PAF receptor antagonists, CV 6209 [1. 4] or WEB 2086 [5] reduce the basal PGI2 generation in both guinea pig [6] and rat peritoneal macro phages [7] by a mechanism which is clearly distinguishable from direct effects on either phospholipase A2, cyclo-oxygenase or PGI2 synthase [7], The lack of response to exoge nous PAF in rat macrophages is seemingly difficult to reconcile with a specific effect of the PAF receptor antagonists on the basal PGI2 generation.…”
Section: Introductionmentioning
confidence: 99%